ASSESSING THE INPUT-PROCESS-OUTPUT MODEL FOR QUALITY MANAGEMENT IN ASEAN UNIVERSITIES: PERSPECTIVES OF CHINESE STUDENTS ABROAD - Zhao, Xingran; Lertlit, Supinda (LPPM Universitas Jambi, 2025)
The aim of the study is to assess how well the input-process-output (IPO) model explains the satisfaction levels of Chinese students regarding their academic experiences in Association of Southeast Asian Nations (ASEAN) countries. Employing a quantitative methodology, the research gathered data through an online survey from a voluntary response sample of 61 Chinese students in ASEAN institutions. The findings indicate statistically significant relationships between the IPO model’s components – input factors (p=0.14), process factors (p=0.00), output factors (p=0.028) – the students’ satisfaction. The study reveals that these factors critically influence the quality management of ASEAN universities in meeting the expectations of Chinese students. The results underscore the importance of aligning university offerings in terms of academic, cultural, social inputs, processes, outputs with the needs of Chinese students. The article concludes with recommendations for ASEAN universities to enhance their educational frameworks by closely aligning them with the social, cultural, academic expectations of Chinese students to encourage positive referrals.